EXPRESSIVISM AND MORAL CERTITUDE - Bykvist, K; Olson, J (2009)
Michael Smith has recently argued that non-cognitivists are unable to accommodate crucial structural features of moral belief, and in particular that non-cognitivists have trouble accounting for subjects' certitude with respect to their moral beliefs. James Lenman and Michael Ridge have independently constructed 'ecumenical' versions of non-cognitivism, intended to block this objection. We argue that these responses do not work. If ecumenical non-cognitivism, a hybrid view which incorporates both non-cognitivist and cognitivist elements, fails to meet Smith's challenge, it is unlikely that 'purer' and more familiar versions of non-cognitivism will succeed. © 2008 The Authors.